ANALYSIS OF OVER CURRENT RELAY AND GROUND FAULT RELAY PROTECTION SYSTEM IN SUB-STATION SP-2 TANAH MIRING USING RELAY COORDINATION WITH ETAP BASED - Soetjipto Soewono; Enni Noprianti (STMIK Pringsewu Lampung, 2020)
Short-circuit often occur in electricity sub-station SP-2 Tanah Miring, Merauke -Papua which caused by malfuction of Over Current Relay (OCR) and Ground Fault Relay (GFR). In enhancing the performance, it takes analysis of relay coordination using ETAP. At maximum load of feeder SP-9 (917 A) an OCR setting is 4.5 A with TMS 0.46 seconds, GFR setting is 4.58 A with TMS 0.17 seconds. At minimum load (324 A) OCR setting is 1.62 A with TMS 0.29 seconds as for the GFR setting is 1.62 A with TMS 0.22 seconds. At the maximum load of feeder Kebun Cokelat (995 A) an OCR setting is 4.97 A with TMS 0.46 seconds as for GFR set is 4.97 A with TMS 0.17 seconds. At minimum load 100 A, OCR setting is 0.5 A with TMS 0.43 seconds while GFR setting is 0.5 A with TMS 0.35 seconds. Furthermore, if the minimum load reach 98 A then the coordination time of GFR and OCR is 0,5 seconds. This analysis found that relay prohibited to operate above 1100 A (maximum) and below 98 (minimum) due to if it working out of the load range then the coordination time would not meet the manual standard.